2012
DOI: 10.1371/journal.pone.0052220
|View full text |Cite
|
Sign up to set email alerts
|

Sponge-Microbe Associations Survive High Nutrients and Temperatures

Abstract: Coral reefs are under considerable pressure from global stressors such as elevated sea surface temperature and ocean acidification, as well as local factors including eutrophication and poor water quality. Marine sponges are diverse, abundant and ecologically important components of coral reefs in both coastal and offshore environments. Due to their exceptionally high filtration rates, sponges also form a crucial coupling point between benthic and pelagic habitats. Sponges harbor extensive microbial communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 115 publications
4
46
0
1
Order By: Relevance
“…Together, these results suggest a context dependency in either the composition of the active members of the sponge microbiome or in sponge‐microbial interactions (Fiore et al ; Maldonado et al ; Thacker and Freeman ). Traditionally the microbial community within sponges has been considered spatially and temporally stable (Erwin et al ; Simister et al ). However, recent work has shown that the active members of sponges' microbial communities can change, sometimes over short temporal scales (Zhang et al ; Fiore et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results suggest a context dependency in either the composition of the active members of the sponge microbiome or in sponge‐microbial interactions (Fiore et al ; Maldonado et al ; Thacker and Freeman ). Traditionally the microbial community within sponges has been considered spatially and temporally stable (Erwin et al ; Simister et al ). However, recent work has shown that the active members of sponges' microbial communities can change, sometimes over short temporal scales (Zhang et al ; Fiore et al ).…”
Section: Discussionmentioning
confidence: 99%
“…While many sponge species host highly stable microbiomes irrespective of environment37383940, recent research has also indicated that shifts in the sponge-associated microbial community may confer a mechanism for local host acclimation to different environmental conditions41. The large shifts in the microbiome of C. foliascens and C. orientalis under low light conditions, including the appearance of novel photosynthetic microorganisms under highly light attenuated conditions (DLI of 0.8 mol photons m −2 d −1 ), may indicate an attempt at symbiont shuffling to a community better able to function under reduced irradiance.…”
Section: Discussionmentioning
confidence: 99%
“…Similar resistance has been seen in other host-symbiont systems. For example, when exposed to thermal, nutrient, and food shortage stressors, no clear changes in sponge symbiont communities have been observed, even though these stressors can lead to host death in some instances (47,48).…”
Section: Discussionmentioning
confidence: 99%